(untitled) (Research, Society and Development, 2020)
The geological-geotechnical characterization of slopes on highways is important for the safety of the road, as these studies make it possible to develop prevention and warning programs and the implementation of works to reduce hazard in these undertakings. Thus, this paper aimed at the geological-geotechnical characterization and assessment of the hazard of rockfall from the slopes located on the BR-262 highway, between Betim and Nova Serrana, in Minas Gerais. Regarding the classification of rock mass, the RMR, Q-System and GSI systems were applied. Subsequently, kinematic analysis, stability analysis were carried out and finally slopes were ranked according to the danger of falling blocks. In none of the slopes the RMR was lower than the regular one. The results of the other classifications were in agreement with the RMR. Safety factors indicated that the slopes are stable. The slope with the highest degree of danger was the P4 - A slope and the one with the least danger was the PM1 slope.